Kekerasan Dalam Pacaran Pada Remaja Perempuan - Fenita Purnama Sari Indah; Nur Hasanah; Putri Handayani Setyaningsih; Rita Dwi Pratiwi; Lela Kania Rahsa Puji (Edu Masda Journal, 2020)
Sexual violence against women is the most common form of violence against women in dating relationships. The highest number of perpetrators of sexual violence in the realm of personal relationships is boyfriends with the largest reporting of 1,528 cases. The objective of this study was to analyze the knowledge, attitudes and actions of dating violence received by girls. This study used a quantitative approach, with a cross sectional design. The research sample was 150 respondents at SMK Sasmita Jaya 1, South Tangerang City. The results showed that 61 respondents (40.6%) had poor knowledge, 137 respondents (91.3%) had poor attitudes, and 5 girls who had experienced violence in dating (3,3%). The results of statistical tests showed that there was no relationship between knowledge and violence in dating (p-value = 0.068> 0.05) and there was no relationship between attitudes and violence in dating (p-value = 0.359> 0.05). Suggestions to the next researchers are that it is better to explore more factors related to dating violence, for example self image factors, self efficacy and others.